The Intermediate-mass Black Hole Reverberation Mapping Project: First Detection of Mid-infrared Lags in Prototypical Intermediate-mass Black Holes in NGC 4395 and POX 52 - Jingbo Sun; Hengxiao Guo; Wenwen Zuo; Paulina Lira; Minfeng Gu; Philip G. Edwards; Shu Wang; Jamie Stevens; Tao An; Samuzal Barua; Zhen-yi Cai; Haicheng Feng; et al. (The Astrophysical Journal Letters)
The search for robust evidence of intermediate-mass black holes (IMBHs) is crucial for understanding the black hole seeding process and the formation of supermassive black holes in the early Universe. NGC 4395 and POX 52 are two prototypical IMBH hosts, both exhibiting multiline evidence of low-mass black hole activity. Here we report the first detection of mid-infrared lags in response to optical variability, with measurements of $3.{0}_{-1.9}^{+2.4}$ days for NGC 4395 and $35.{2}_{-11.7}^{+14.2}$ days for POX 52 at 3.4 μ m, respectively, using archival optical data and observations from the Wide-field Infrared Survey Explorer. This detection provides the first reverberation evidence of low-mass black hole activity in POX 52. The time lags of these two low-mass, low-luminosity active galactic nuclei (AGNs) generally follow the extent of the R _dust – L _5100 relation found in higher-mass AGNs. Based on an empirical relation between the broad-line region and dusty torus size, we constrain the black hole mass of POX 52 to log( M _BH / M _⊙ ) = 5.5 ± 0.37 (systemic and statistical errors), confirming its IMBH nature. Furthermore, long-term optical continuum monitoring of POX 52 reveals a mild interband lag of ≲1 day. However, no significant intranight variability was detected during its one-night, high-cadence monitoring, which we attribute to the longer duty cycle of fast variability in POX 52 compared to that in NGC 4395.